Risk Factors and Underlying Mechanisms for Venous Stasis Syndrome: A Population-Based Case-Control Study - Ashrani, Aneel A. (2009)
BACKGROUND: Venous stasis syndrome may complicate deep vein thrombosis (DVT; i.e., post-phlebitic syndrome), but in most cases, venous stasis syndrome is not post-phlebitic. OBJECTIVE: To determine risk factors (including prior DVT) for venous stasis syndrome, and to assess venous outflow obstruction and venous valvular incompetence as possible mechanisms for venous stasis syndrome. DESIGN: Case-control study nested within a population-based inception cohort. POPULATION: 232 Olmsted County, MN residents with a first lifetime venous thromboembolism (VTE), and 133 residents without VTE. MEASUREMENTS: Questionnaire and physical examination for venous stasis syndrome; strain gauge outflow plethysmography, venous continuous wave Doppler ultrasonography and passive venous drainage and refill testing for venous outflow obstruction and venous valvular incompetence. RESULTS: Altogether, 161 (44%), 43 (12%), and 136 (38%) subjects respectively, had venous stasis syndrome, venous outflow obstruction and venous valvular incompetence. Independent risk factors for venous stasis syndrome included increasing patient age and body mass index (BMI), prior DVT, longer time interval since DVT, and varicose veins. Both venous outflow obstruction (p=0.003) and venous valvular incompetence (p<0.0001) were strongly associated with venous stasis syndrome. Increasing age and prior DVT were significantly associated with venous outflow obstruction, while prior DVT, varicose veins and venous stasis syndrome diagnosed prior to the incident DVT were significantly associated with venous valvular incompetence. The risks of venous outflow obstruction, venous valvular incompetence and venous stasis syndrome were higher with left leg DVT. CONCLUSIONS: Increasing patient age and BMI, prior DVT (particularly left leg DVT), longer time interval since DVT and varicose veins are independent risk factors for venous stasis syndrome. Venous stasis syndrome related to DVT is due to venous outflow obstruction and venous valvular incompetence, while venous stasis syndrome related to older age and to varicose veins is due to venous outflow obstruction and to venous valvular incompetence, respectively.